UKRAINIAN STATE BETWEEN SCYLLA AND CHARYBDIS OF CHALLENGES OF PAST AND FUTURE: WHETHER OWN PARADIGM OF DEVELOPMENT IS POSSIBLE? - Авксентьєва, Т.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The problem of stability/instability of modern state and factors of overcoming the destructive phenomena, the most important among them are excessive growth of the phenomenon of randomness in political development are considered. Challenges for the Ukrainian state, connected with the forces of tradition and modernization are analysing. Significant attention is paid to the growth of the state's role in forming of common sociocultural field as a necessary factor in creating the conditions for political stabilization.